Socioemotional wealth and performance in private family firms - Razzak, Mohammad Rezaur; Jassem, Suaad (Emerald, 2019)
Purpose: Although family business literature acknowledges that family firms owners are motivated by a set of socioemotional wealth (SEW) goals along with firm-centric business goals, yet a consistently predictable pattern of relationship between SEW and financial wealth is yet to be discerned. The purpose of this paper is to propose a theoretical model based on the stakeholder approach to suggest that family commitment mediates the association between the dimensions of SEW and firm performance. Design/methodology/approach: A set of hypotheses are proposed that are tested using structural equation modeling with data collected from 357 medium to large sized privately held family firms in Bangladesh. The data analysis is done with SmartPLS (v.3.2). Findings: The results indicate that family commitment partially mediates the relationships between family control and influence, family identification, emotional attachment and renewal of family bonds through dynastic succession and firm performance. The only non-significant relationship was between binding social ties and firm performance. The results provide a more nuanced understanding of the link between SEW goals and firm performance, and present important implications for theory and practice. Research limitations/implications: The cross-sectional nature of the study exposes it to the specter of common method bias despite the fact that procedural remedies were initiated to minimize the impact of such occurrence. A longitudinal study with data obtained from multiple individuals at different levels of the organization would possibly yield more robust findings. Furthermore, in the absence of a multi-country and multi-sector analysis, a broad generalization of the findings may not be feasible. Practical implications: The knowledge that family identity, emotional attachment and renewal of family bonds through dynastic succession may be leveraged to enhance the commitment of subsequent generation of family firm owners to the firm that may be pertinent to incumbents who desire to see their successors more engaged in the family enterprise. Furthermore, knowing that excessive focus on family control over the firm leads to negative outcomes is also pertinent to family firm leaders. Social implications: Survival of family businesses is vital to the global economy as one of the primary drivers of global GDP growth and source of new employment. Policy makers can benefit from the findings of this study to customize policies that take into cognizance the importance of SEW owners of family firms and the fact that some of these SEW goals actually benefit the firm in terms of enhanced commitment to the enterprise and consequently superior firm performance. Originality/value: The role of family commitment as a mediator between SEW and firm performance has not been dominant in the literature. By providing a finer-grained understanding of how family commitment accounts for the relationship between family-centric non-economic goals such as SEW and firm-centric goals such as business performance, the study presents a theoretical link between sociomemotional wealth and financial wealth in the context of private family firms. © 2019, Emerald Publishing Limited.